Enhancing Student’s Communication Skills in Writing Biology Practical Reports Using Flashcards - Khairunnissa, Afifah Zulfa; Fitriana, Desi Eka Nur; Rifqiawati, Ika; Maryani, Nani (Universitas Sultan Ageng Tirtayasa, 2024)
This study aimed to determine students' written communication skills in writing practicum reports using flashcards. The research was conducted on grade 11th high school students with a simple random sampling technique. The research method used was an experimental method with Posttest-Only Control Group Design. In the experimental group, students were instructed to use flashcards to write their practicum reports, while the control group used conventional methods, writing on paper as usual. Students were then asked about their experience with a questionnaire. Students' reports on flashcards were scored and analyzed. The results showed that using flashcards significantly improved students’ written communication skills in writing practicum reports. This improvement was reflected in comparing post-test results between the experimental and control groups. In addition, students also responded positively to flashcards to improve their practicum report writing skills. The findings of this study contribute to the practical and theoretical understanding of effective teaching methods for writing, especially in the context of practicum reports. This study gives an insight into students' communication skills in writing that can be improved by applying innovative learning strategies.